Experimental Investigation of Oblique Impact Behavior of Adhesively Bonded Composite Single-Lap Joints - Atahan, M. Gokhan; Apalak, M. Kemal (Springer, 2022)
Determining the impact behavior of adhesive joints allows the designing of high-strength joints. Therefore, the dynamic behavior of adhesive joints has recently become a trending research topic. The study aims to examine the impact behavior and damage mechanism of the adhesively bonded composite joints, taking into account different impact angles. The mechanical behavior of adhesively bonded glass-fiber reinforced laminated composite single-lap joints under bending impact load was experimentally determined via a drop weight impact test machine. The effects of impact angle (theta = 0 degrees, 10 degrees, 20 degrees, 30 degrees), fiber angle (phi = 0 degrees, 45 degrees, 90 degrees), and overlap length (b = 25, 40 mm) on the impact behavior of the joints were investigated. These parameters were determined to affect the impact behavior of the joint and the damage characterization. The highest contact force occurred in the joints with 0 degrees fiber angle having the highest bending strength, and the lowest contact force occurred in the joints with 90 degrees fiber angle having the lowest bending strength. Due to the increase in the impact angle, the maximum contact force value in the joints decreased, while the total contact time increased. The increase in overlap length had little effect on the maximum contact force and total contact time, and the vertical displacement decreased due to the increasing bending stiffness. The unbalanced joint with 45 degrees fiber angle was forced to rotate around its axis due to in-plane unbalanced shear stress distributions induced by the bending impact load. The unbalanced shear stress distribution caused shear damage at the fiber-matrix interface and the top composite-adhesive interfaces. In joints with 0 degrees fiber angle, the impact energy was mostly met with adhesive damage, while the composite adherend was damaged as a result of increased shear stresses in the matrix region for the joints with 90 degrees fiber angle.
Atahan, Mithat Gokhan/0000-0002-8180-5876; Apalak, Mustafa Kemal/0000-0002-3263-5735
Keywords: Low Speed Impact; Oblique Impact; Adhesive Joint; Composite Joint; Single Lap Joint